Measuring developer contribution from software repository data - Gousios, Georgios; Kalliamvakou, Eirini; Spinellis, Diomidis; Nancy, Pouloudi (2008 Mining Software Repositories, 2008)
Apart from source code, software infrastructures supporting agile and distributed software projects contain traces of developer activity that does not directly affect the product itself but is important for the development process. We propose a model that, by combining traditional contribution metrics with data mined from software repositories, can deliver accurate developer contribution measurements. The model creates clusters of similar projects to extract weights that are then applied to the actions a developer performed on project assets to extract a combined measurement of the developer's contribution. We are currently implementing the model in the context of a software quality monitoring system while we are also validating its components by means of questionnaires.